An Automated Image-Based Dietary Assessment System for Mediterranean Foods - Fotios S. Konstantakopoulos; Eleni I. Georga; Dimitrios I. Fotiadis (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: The modern way of living has significantly influenced the daily diet. The ever-increasing number of people with obesity, diabetes and cardiovascular diseases stresses the need to find tools that could help in the daily intake of the necessary nutrients. Methods: In this paper, we present an automated image-based dietary assessment system of Mediterranean food, based on: 1) an image dataset of Mediterranean foods, 2) on a pre-trained Convolutional Neural Network (CNN) for food image classification, and 3) on stereo vision techniques for the volume and nutrition estimation of the food. We use a pre-trained CNN in the Food-101 dataset to train a deep learning classification model employing our dataset Mediterranean Greek Food (MedGRFood). Based on the EfficientNet family of CNNs, we use the EfficientNetB2 both for the pre-trained model and its weights evaluation, as well as for classifying food images in the MedGRFood dataset. Next, we estimate the volume of the food, through 3D food reconstruction of two images taken by a smartphone camera. The proposed volume estimation subsystem uses stereo vision techniques and algorithms, and needs the input of two food images to reconstruct the point cloud of the food and to compute its quantity. Results: The classification accuracy where true class matches with the most probable class predicted by the model (Top-1 accuracy) is 83.8%, while the accuracy where true class matches with any one of the 5 most probable classes predicted by the model (Top-5 accuracy) is 97.6%, for the food classification subsystem. The food volume estimation subsystem achieves an overall mean absolute percentage error 10.5% for 148 different food dishes. Conclusions: The proposed automated image-based dietary assessment system provides the capability of continuous recording of health data in real time.